Adolescent brain maturation and the neuropathological effects of binge drinking: A critical review - Tetteh-Quarshie, Samuel; Risher, Mary-Louise (Frontiers in Neuroscience, 2023)
Adolescence is a transitional stage marked by continued brain development. This period is accompanied by physical and neurochemical modifications in the shape and function of the hippocampus, prefrontal cortex, and other limbic system structures. Brain maturation during adolescence, which is typically governed by intrinsic factors, can be dramatically altered by environmental influences such as drugs and alcohol. Unlike many other addictive substances, binge drinking is very common and normative among teenagers and young adults. This repeated pattern of excessive alcohol consumption in adolescents has been shown to cause behavioral changes and neurocognitive impairments that include increased anxiety, risky decision-making, and learning deficits, which could lead to the development of alcohol use disorder (AUD). This manuscript highlights factors that lead to adolescent binge drinking, discusses maturational changes that occur in an adolescent’s brain, and then evaluates the effect of adolescent alcohol consumption on brain structure, function, and neurocognitive abilities in both human studies and animal models. The impact of gender/sex and COVID-19 are briefly discussed. Understanding the factors that promote the onset of adolescent binge drinking and its undesirable consequences could serve as a catalyst for developing therapeutic agents that would decrease or eradicate the damaging effects of alcohol on an adolescent brain.